Credentialing for participation in clinical trials - Followill, David S.; Urie, Marcia M.; Galvin, James M.; Ulin, Kenneth; Xiao, Ying; Fitzgerald, Thomas (Frontiers in Oncology, 2012)
The National Cancer Institute (NCI) clinical cooperative groups have been instrumental over the past 50 years in developing clinical trials and evidence-based clinical trial processes for improvements in patient care. The cooperative groups are undergoing a transformation process to launch, conduct, and publish clinical trials more rapidly. Institutional participation in clinical trials can be made more efficient and include the expansion of relationships with international partners. This paper reviews the current processes that are in use in radiation therapy trials and the importance of maintaining effective credentialing strategies to assure the quality of the outcomes of clinical trials. The paper offers strategies to streamline and harmonize credentialing tools and processes moving forward as the NCI undergoes transformative change in the conduct of clinical trials.